THE MIDDLE JURASSIC OSTRACOD GENUS PARADOXORHYNCHA CHAPMAN FROM AUSTRALIA AND ARGENTINA: A GONDWANAN ZOOGEOGRAPHICAL ENIGMA (Ameghiniana, 2014)
From observations on early Middle Jurassic Australian and Argentinian material, the genus Paradoxorhyncha Chapman, 1904 is removed from Progonocytheridae, Progonocytherinae and placed in Cytheruridae, Cytheroptherinae. Five species are included: P. foveolata Chapman (type species), P. jurassica (Chapman), P. australiense (Chapman), Paradoxorhyncha sp. and P. neuquenensis (Ballent). AIl except the last, which is Argentinian, are restricted to Western Australia. This genus represents an endemic faunal element in the Southern Hemisphere. A migrationary model is put forward to account for the enigmatically disjunct nature of the occurrence of this taxon.